Percepções e vivências sobre origem da vida e biologia evolutiva de docentes de escolas públicas do ensino médio de Alagoa Nova-PB, Brasil - Santos, Danilo Marcos dos (2023)
The origin of life and biological evolution are central topics in biology. Teaching and understanding these topics are fundamental to comprehending events in the natural sciences and other fields of knowledge. Therefore, the BNCC (National Curricular Common Base) suggests that these topics should be approached in an interdisciplinary manner. This research aimed to analyze the perspectives of teachers from two high schools in the city of Alagoa Nova PB regarding biological evolution and the origin of life, reflecting on the experiences reported by these teachers, both personally and in the classroom. To achieve this, a semi-structured questionnaire with objective and subjective questions was utilized. Subsequently, the methodology proposed by Bardin was applied, enabling the grouping and categorization of the obtained answers. The results indicated that despite the origin of life and biological evolution being central topics in biology and other fields of knowledge, a larger proportion of teachers claim to be unfamiliar with Charles Darwin's theory of evolution. Among the teacherssurveyed, those with over 10 years of classroom experience are more likely to believe in it. Additionally, over half of the teachers believe that the origin of life is of divine nature, but they also perceive that science and religion can coexist as parallel subjects. Despite the central role of evolutionary biology, many teachers resort to their religious teachings to explain phenomena or formulate their own explanations by combining scientific and religious perspectives. This research highlights that, although teachers may uphold the scientific view as an explanation for natural phenomena, their religious beliefs can sometimes interfere with their responses and this is a matter of concern, as a significant portion of teachers tend to create their own theories to explain scientific facts.